PERANCANGAN IT MASTER PLAN STUDI KASUS : WAHANA LINGKUNGAN HIDUP INDONESIA (WALHI) - Riffa Haviani Laluma (STMIK Mardira Indonesia, Bandung, 2015)
WALHI aware of the tendency of environmental damage more massive and complex both in rural and urban areas. Deteriorating environmental conditions openly acknowledged influence the social dynamics of political and socioeconomic conditions both at the community, regional, and national levels. To ensure the sustainability of future generations needed a strong social movements and widespread. Future generations are entitled to a good environment and healthy. For that generation now responsible for maintaining and improving the quality of a better environment. Porter Competitive models used to understand and evaluate the environmental structure and threats in a type of business. Model Porter explains that there are five forces that determine kemenarikkan and profitability of the industry, namely: Competitors in the same industry (Intraindustry rivalry), The strength of the consumer (The bargaining power of buyers), Strength of the suppliers (The bargaining power odd suppliers ), threat of new competitors (The threat of new entrants), threats from supporters of the product or service (The threat of substitute product or service). Keywords: Competitive Model Porter, Intraindustry Rivalry, Power Of Buyers, Power Od Suppliers, Substitute Product Or Service Abstrak WALHI sadar kecenderungan kerusakan lingkungan hidup semakin masif dan kompleks baik di pedesaan dan perkotaan. Memburuknya kondisi lingkungan hidup secara terbuka diakui mempengaruhi dinamika sosial politik dan sosial ekonomi masyarakat baik di tingkat komunitas, regional, maupun nasional. Untuk menjamin keberlanjutan kehidupan generasi mendatang dibutuhkan gerakan sosial yang kuat dan meluas. Generasi mendatang berhak atas lingkungan hidup yang baik dan sehat. Untuk itu generasi sekarang bertanggungjawab mempertahankan dan meningkatkan kualitas lingkungan yang lebih baik. Model Kompetitif Porter digunakan untuk memahami dan mengevaluasi struktur lingkungan dan ancaman dalam suatu jenis usaha. Model Porter menjelaskan bahwa ada lima kekuatan yang menentukan kemenarikkan dan keuntungan suatu industri, yaitu : Pesaing dalam industri yang sama (Intraindustry rivalry), Kekuatan dari para konsumen (The bargaining power of buyers), Kekuatan dari para pemasok (The bargaining power od suppliers), Ancaman dari pesaing baru (The threat of new entrants), Ancaman dari pendukung produk atau layanan (The threat of substitute product or service). Kata Kunci: Model Kompetitif Porter, Intraindustry Rivalry, Power Of Buyers, Power Od Suppliers, Substitute Product Or Service